If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5p + 3q = 2 Solving 5p + 3q = 2 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-3q' to each side of the equation. 5p + 3q + -3q = 2 + -3q Combine like terms: 3q + -3q = 0 5p + 0 = 2 + -3q 5p = 2 + -3q Divide each side by '5'. p = 0.4 + -0.6q Simplifying p = 0.4 + -0.6q
| x+2=-40+7x | | 6+2x=-3x+26 | | (X-8)/12 | | -23t=138 | | (x+1)+2x+(x-4)=7.3 | | (2x+5)+(4x-25)=45 | | log(4x^2)= | | 3x+4y-3= | | -52=47 | | 3xsquare-3x+12=0 | | 6x+8=-28+2x | | 5+4a=3 | | 7(x+8)=7(x+11) | | .5(x+8)=2x+16 | | 7(x-8)=56x-8 | | 3x-2/5=x-9/2 | | -2x+7=4x+31 | | factorv^3+512= | | 7(x-2)=2(5-x) | | 3x-2/5=x-9 | | 2n=n+0.1 | | v^3+512= | | 0.6+n=n+0.1 | | 4(8x-1)=19+32x | | v/10=10 | | 3p-4=5 | | 4m+19m=92 | | -6x-7=2x-15 | | u=v-20 | | 5-3(x+4)=5x+9 | | 4(8x-1)=19+32 | | 0.42-0.03=3.33-x |